Effective Methods for MAC Protocol Routeing in Cyber-Physical-System-Enabled Networks - Chauhan, Rahul (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
A Cyber Physical System (CPS) is a networking environment that uses wireless communication to keep tabs on the flow of physical events and take corrective measures as needed to keep the entire thing running smoothly. Cyber-physical systems, or CP-systems, are often referred to as "smart systems" because of the value they provide by providing intelligent services during emergency circumstances. Since Medium Access Control (MAC) plays a significant role in CPS applications, any modifications to MAC will have an effect on CPS performance. This thesis proposes a number of strategies for improving MAC in order to boost wireless network performance. Despite the fact that CPS is a hybrid network, efforts have been made to include some wiggle room into the more conventional "back off" process. Energy Hashed Virtual Back off Algorithm (EHVBA) is used, which is a back off approach that conserves power. This algorithm incorporates energy as a new method parameter to boost CPS performance. However, because MAC is crucial in CPS networks, the standard back off procedure needs some flexibility. To prevent interference in the unspotted mode of the 802.15.4 protocol, we give each device a priority and counter. Even though IEEE 802.15.4 may be breached by competing wireless technologies, problems only arise after a certain phase of medium access has been resolved.